Peer group supervision as an adjunct to individual supervision: an investigation of models of learning - Akhurst, Jacqueline Elizabeth (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
Supervision of practice makes an important contribution to the development of psychotherapeutic skills in the training of psychologists (Bernard and Goodyear, 1998). Much research has, until recently, focussed on dyadic, hierarchical models of supervision, even though other forms of supervision have been developed. Peer group supervision has had little attention in the literature, although it is a common form of supervision utilised by psychologists in practice (Lewis, Greenburg and Hatch, 1988). A review of the literature considers the purposes of supervision; elements of dyadic supervision; various forms of group, peer and peer group supervision; and the leaming process in supervision. The development and implementation of a peer supervision group (pSG) of intern psychologists within the training setting of a University is described in this study. The PSG model was developed from the model proposed by Wilbur, Roberts-Wilbur, Morris, Betz and Hart (1991). Transcripts from nine audio-taped PSG sessions were analysed, and a comparison with four audio-taped dyadic supervision sessions was then undertaken. Grounded Theory methodology was employed in the design of the study and analysis of the data. The form and content of the two models of supervision were examined, with particular attention to the perspective of the trainees' learning experiences. The relative merits of both forms of supervision were assessed, and this analysis clearly demonstrates that peer group supervision has the potential to complement dyadic supervision by contributing differing learning experiences. A model of key influences upon, and effects of, participation in the two forms of supervision has been developed. Suggestions are made of ways in which dyadic supervision may be optimised, and recommendations for further development of the PSG emerge. The results were then considered from a neo-Vygotskian perspective. This enabled the findings to be linked to a comprehensive theory of learning, pointing to the key role of speech in thinking, and the contributions of the various forms of dialogue to deepened understandings. The discussion includes: consideration of techniques which enable trainees to obtain assistance from both more experienced practitioners as well as from their peers; an exploration of aspects of subjectivity and intersubjectivity; and contextual influences which have bearing on the study. This study identifies the need for further consideration of the supervision process in South Africa, and makes recommendations for the training of supervisors. The neo-Vygotskian model offers great promise both as a framework for understanding the leaming process in. supervision, and for developing guidelines for enhancing supervisory practice.
Keywords: Peer-group tutoring of students; Psychotherapy -- Study and teaching -- Supervision; Psychology -- Supervision of